Analysis of etalon filter in quantum memory. Issue 5 (11th April 2022) - Li, Ruiyang; Lei, Xing; Ma, Lixia; Yan, Zhihui; Jia, Xiaojun
Abstract: For quantum on‐demand storage and retrieval of nonclassical light, the memory noise at shot noise limit is a necessary condition. And an optical filter is widely used to filter out the strong control mode when the signal mode is maintained. Thus we construct and analyze an etalon filter with the planar monolithic geometry. The signal mode resonant with the etalon is selected and the unwanted modes are filtered out by precisely controlling the etalon temperature. The noise suppression factor for control mode is 0.053 while the transmissivity for signal mode is 97% with a fluctuation of 1.7% within 30 min. Our analysis can provide a direct reference for optimizing the performance of quantum memory.